(untitled) (Journal of Business Management and Accounting, 2018)
Asymmetry of information involves the possession of information in different ways between the most informed stakeholders and the uninformed stakeholders which may affect the performance of companies. Using agency theory, this study investigates the relationship between corporate governance mechanisms and level of information asymmetry in UAE based on 64 annual reports for the year ended 2010. The findings indicate that board size and information asymmetry are positively related among UAE listed companies, while board ownership and company size are negatively related with information asymmetry. These results suggest that large size of the board of directors may lead to information asymmetry because they seem to be unable to monitor the management and protect the interest of shareholders. In addition, evidence of high information asymmetry among UAE companies imply that the implementation of the Code of Corporate Governance seems to be less likely to resolve agency problems due to asymmetric information.